Analisis Mugāyarah antara Mubtada’ dan Khabar dalam Al-Qur’an: Tinjauan Nahwiyah : Analisis Mugāyarah Antara Mubtada' dan Khabar dalam Al-Qur'an: Perspektif Gramatikal (Nahwī) - naili, Muhammad; Kurnia, Ulfa (ELOQUENCE : Journal of Foreign Language, 2025)
Background: The phenomenon of mugāyarah in the nominal sentence (jumlah ismiyyah) structures of the Qur’an reflects a fascinating linguistic dynamic that warrants exploration from the perspective of Arabic grammar (nahwu). Purpose: This study aims to analyze the forms and functions of mugāyarah between the mubtada’ (subject) and khabar (predicate) in the Qur’an, using both syntactic and semantic approaches. Method: A descriptive qualitative approach was employed, using a textual study design. Data were sourced from Qur’anic verses containing nominal sentences, selected through purposive sampling of 20 verses that demonstrate the mugāyarah phenomenon. The primary instrument was classical Arabic linguistic analysis, supported by AntConc software to visualize word distribution. Data analysis was conducted through syntactic and semantic approaches grounded in classical Arabic linguistic theory and tafsir. Results and Discussion: The findings reveal that mugāyarah in the relationship between mubtada’ and khabar functions as a rhetorical and semantic strategy that enhances the message of the verses, rather than constituting a grammatical anomaly. These grammatical variations highlight the richness of Qur’anic linguistic structures and address a gap in linguistic studies concerning semantically valid deviations. Conclusions and Implications: This study concludes that mugāyarah enriches the meaning and adds deeper linguistic dimensions to the Qur’an. The findings have implications for the development of Arabic linguistic studies and linguistic exegesis in understanding sacred texts.